Governance of FDI and the East Asian Economic Community - Zdenek Drabek (Elsevier, 2021)
Policy makers in the Asia Economic Community (AEC) engaged in the integration of the countries in the region have so far focused their attention on measures affecting commodity markets. Integration of investment activities should follow in the future. To achieve integration, the policy makers will have to harmonize investment rules. This paper discusses some of the major theoretical and empirical issues of investment governance. The theory is quite clear that, in most cases, cooperation and harmonization of investment rules should be beneficial for countries, a conclusion that is strongly supported by empirical evidence. However, the theory is less clear about specific rules. Though it is still evolving, the theory does provide useful guidance to policy makers in the AEC for negotiating more complete and efficient contracts involving foreign investment.